2020
DOI: 10.1016/j.annonc.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance to selective RET tyrosine kinase inhibitors in RET fusion-positive non-small-cell lung cancer

Abstract: Background: Rearranged during transfection (RET) gene fusions are a validated target in non-small-cell lung cancer (NSCLC). RET-selective inhibitors selpercatinib (LOXO-292) and pralsetinib (BLU-667) recently demonstrated favorable antitumor activity and safety profiles in advanced RET fusion-positive NSCLC, and both have received approval by the US Food and Drug Administration for this indication. Insights into mechanisms of resistance to selective RET inhibitors remain limited. Patients and methods: This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 39 publications
3
104
1
1
Order By: Relevance
“…These RTKs then switch on the same downstream signalling pathways that would normally be activated by the mutant EGFR if it was not inhibited by the drug (that is, the RAF–MEK–ERK and PI3K–PDK1–AKT pathways) 109 . This phenomenon has also been observed in other NSCLC settings where the cells respond to inhibitors of mutant ALK by overexpressing the EGFR or KIT receptor, while MET amplification has been identified as an emerging resistance mechanism to RET inhibitors 110 . In breast cancer, resistance to agents targeting HER2 overexpression have similarly been associated with switching to alternative RTKs including MET, HER3 and IGF1R 111 , 112 .…”
Section: Resistance To Protein Kinase Inhibitorsmentioning
confidence: 59%
“…These RTKs then switch on the same downstream signalling pathways that would normally be activated by the mutant EGFR if it was not inhibited by the drug (that is, the RAF–MEK–ERK and PI3K–PDK1–AKT pathways) 109 . This phenomenon has also been observed in other NSCLC settings where the cells respond to inhibitors of mutant ALK by overexpressing the EGFR or KIT receptor, while MET amplification has been identified as an emerging resistance mechanism to RET inhibitors 110 . In breast cancer, resistance to agents targeting HER2 overexpression have similarly been associated with switching to alternative RTKs including MET, HER3 and IGF1R 111 , 112 .…”
Section: Resistance To Protein Kinase Inhibitorsmentioning
confidence: 59%
“…Many patients with ALK, ROS1, or RET fusion benefiting from matched targeted therapy will develop acquired resistance within 1 year, and a small fraction of patients were found to have progressive disease (PD) as their best response owing to intrinsic resistance. [5][6][7] High-throughput next-generation sequencing (NGS) is ideal for uncovering diverse genetic events in NSCLC. 8 Target-capture DNA NGS is capable of pinpointing breakpoints to specific base positions in the genome, and thus can identify variable fusion variants.…”
Section: Introductionmentioning
confidence: 99%
“…For patients in which mutations in the RET kinase domain responsible for drug resistance were not detected, evidence exist mostly for the activation of bypass signaling pathways. MET dependence has been reported as a recurring and potentially targetable mechanism of resistance to selpercatinib and pralsetinib [81][82][83]. Preclinical studies have demonstrated that EGFR transduced bypass signals to critical downstream pathways which regulate cell proliferation and survival via ERK and AKT, enabling cancer cells to evade RET inhibitors.…”
Section: Reported Mechanisms Of Off-target Drug Resistancementioning
confidence: 99%